Causes of EFL Learners’ Procrastination: A Classical Grounded Theory - Saber Khooei-Oskooei; Saeideh Ahangari; Zohreh Seifoori (Issues in Language Teaching, 2022)
In the long process of learning English as a foreign language, learners may become exhausted and, if not treated properly, decide to give up learning temporarily and even permanently. Therefore, it seems necessary to explore the reasons for their temporal delays and consider them appropriately to avoid permanent give-ups. As an attempt to determine the reasons for English as a Foreign Language (EFL) learners’ delays, the researchers in the present study explored their contributing factors through application of a classical grounded theory approach which led to the development of Language Learning Procrastination (LLP) theory. The research data were collected through semi-structured interviews from 43 EFL learners in Tabriz, Iran, and were coded in open, selective, and theoretical coding stages through a Constant Comparative Method. The emerged theory involved a core category (i.e., Dilatory Behavior) indicating that EFL learners mostly procrastinate in five domains of doing exercises, preparation for exam, submitting projects, starting up speaking, and learning spelling. Furthermore, three major categories of Learners’ Characteristics, Environmental Conditions, and Task Features as the causes of Dilatory Behavior emerged during the iterative data collection and analysis procedures. The results of the study indicated that both EFL learners’ own characteristics and external factors related to the learning environment and language tasks are significant in shaping the EFL learners’ procrastination. The theory of LLP can be applied in EFL settings to recognize the learners’ sources of Dilatory Behavior and devise appropriate solutions for them.